Zimmer d'Olivier Benyahya: fiction française à l'heure des rivalités communautaires et victimaires - Almeida, José Domingues de (2019)
The short novel Zimmer (2010) by young French Jewish writer Olivier Benyahya raises the pressing question of French identity, particularly through the prism of the complexity, if not the impossibility, of a coherent national identity affirmation and a peaceful coexistence of the Jewish, Black and Arab communities. These communities are engaging in a subliminal and underground struggle based on the claim of victim legitimacy.